Following Foucault’s continuum between war and law in Kosovo: ‘hybrid policing’ and selective criminalization in international policing - Degenhardt, Teresa (Journal of Theoretical and Philosophical Criminology, 2020)
This article examines the case of Kosovo as an important precedent in the development of practices of policing beyond borders–whereby military and policing practices are extended beyond borders with the aim of producing security at a distance. It examines how these practices, led by the global north, implemented as a result of humanitarian military interventions actually worked locally in Kosovo, placing it in the wider theoretical context of Foucault’s work on the continuum between war and law, and critically challenging the representation of the international as a space of law and justice (MacMillan, 2016). It argues that even if the representations of crime and justice have a crucial function in expanding practices of policing beyond borders, contributing to exporting liberal forms of criminal justice to foreign countries to build peace and a liberal society, and support for international criminal justice, the results are far from straightforward. It suggests that these practices of policing beyond borders may be contributing to the production of hybrid forms of policing in which violent contestations to policing and criminalization are prevalent, rather than integration of different forms of justice. This aspect be the re-emergence of war within legal processes but may also be seen as attempts to void the establishment of the liberal peace and of law.